Three-Dimensional Multidetector CT for Anatomic Evaluation of Orbital Tumors - J. Matthew Debnam; Rory R. Mayer; Bita Esmaeli; Jeffrey S. Weinberg; Franco DeMonte; Nandita Guha-Thakurta (Journal of Ophthalmology)
Intricate resection and complex reconstructive procedures often required for primary and metastatic orbital tumors are facilitated by accurate imaging. A three-dimensional (3D) image can be reconstructed from source axial multidetector computed tomography (MDCT) images to visualize orbital tumors. To assess the utility of 3D images in this setting, the 3D images were reconstructed retrospectively for 20 patients with an orbital tumor and compared to two-dimensional (2D) orthogonal MDCT studies. Both types of images were assessed for their capacity to show the bony orbital walls and foramina, extraocular muscles, and optic nerve in the orbit contralateral to the tumor and, in the affected orbit, the extent of the tumor and its relationship to normal orbital contents and associated bone destruction. 3D imaging is most informative when axial images are acquired at 1.25 mm collimation. The optic nerve, extraocular muscles, and well-circumscribed orbital tumors were well visualized on 3D images. On 3D imaging, tumor-associated destruction of the lateral and superior orbital walls was fairly well demonstrated and that of the inferior and medial walls was not. The 3D images provide the surgeon with a comprehensive view of well-circumscribed orbital tumors and its relationship to extraocular muscles, exiting foramina, and the superior and lateral walls.